The Framing of Queen Elizabeth II's Death Notices - Nauka Nayana Prasadini; Tri Winindyasari Palupi (English Language Education Study Program of STKIP PGRI Banjarmasin, 2023)
Death, and delivering news on death, is a difficult subject to be discussed with people. Despite its potential for exploring the topic, it is rarely being brought up in previous research. Researchers note that by understanding the topic, it will show how news outlets frame an issue and how audiences would react to it. One of the most recent examples is the death notices of Queen Elizabeth II, which leads to mixed reactions from audiences around the world. This study looks at how news outlets portrayed the death of Queen Elizabeth II through their death notices. The study uses a qualitative approach, focusing on the news framing aspect. The data were taken from the death notices of Queen Elizabeth II, delivered by several major television news outlets in the United Kingdom. The data were transcribed and analyzed under Swales’ (1990) moves theory and Muhammad’s (2020) death notice moves. The result shows that despite most of the death notices fulfilling several death notice’s moves, the framing of the news may differ depending on the target audiences or the news outlets' bias toward the Royal Family.